Optimization and mechanisms for biodecoloration of a mixture of dyes by Trichosporon akiyoshidainum HP 2023 - Martorell, María Martha (2017)
Trichosporon akiyoshidainum HP2023 is a basidiomycetous yeast isolated from Las Yungas rainforest (Tucumán, Argentina) and selected based on its outstanding textile-dye-decolorizing ability. In this work, the decolorization process was optimized using Reactive Black 5 as dye model. Lactose and urea were chosen as carbon and nitrogen sources through a one-at-time approach. Afterwards, factorial designs were employed for medium optimization, leading to the formulation of a simpler optimized medium which contains in g L−1: lactose 10, yeast extract 1, urea 0.5, KH2PO4 1 and MgSO4 1. Temperature and agitation conditions were also optimized. The optimized medium and incubation conditions for dye removal were extrapolated to other dyes individually and a mixture of them. Dye removal process happened through both biosorption and biodegradation mechanisms, depending primarily on the dye structure. A positive relation between initial inoculum and dye removal rate and a negative relation between initial dye concentration and final dye removal percentages were found. Under optimized conditions, T. akiyoshidainum HP2023 was able to completely remove a mixture of dyes up to a concentration of 300 mg L−1, a concentration much higher than those expected in real effluents.